POSITIVE-PSYCHOLOGICAL CHARACTERISTICS OF ADDRESSING HARASSMENT AND VIOLENCE AGAINST WOMEN IN THE FAMILY: EMPOWERMENT, RESILIENCE, AND HEALING (American Journal of Interdisciplinary Research and Development, 2024)
This scientific article explores the positive-psychological characteristics that emerge in the context of addressing harassment and violence against women in the family. While these forms of abuse have severe negative consequences, it is important to shed light on the positive aspects that can arise from the process of healing and recovery. This article examines the concepts of empowerment, resilience, and healing as positive-psychological characteristics that women can develop in response to family-based harassment and violence. Understanding and promoting these characteristics can contribute to the well-being, recovery, and long-term empowerment of survivors.